Determinants of machinery firms innovation activity - case study from the Czech Republic - Viktor Prokop; Jan Stejskal (European Regional Science Association (ERSA), 2015)
Innovative activities have been considered mandatory for surviving in a dynamic market environment, inter alia in the machinery industry. Nothing has received as much attention as innovation, which has been pinpointed as the fundamental driving force for economic growth and welfare as well as a key factor in competitiveness. Therefore, innovation growth is seen as a mechanism to influence economic growth, and therefore firms capable of increasing their innovation potential benefit from further increasing competitive advantage and economic growth. However, innovations do not arise within one company in isolation. Today, in the so-called knowledge economy, innovation ? more than most other economic activities ? depends on new economic knowledge, which is perceived to be the basic ingredient of the innovative process. It follows that the increased complexity of knowledge processes influences firms, because organizations need to be able to respond to the growing demand for improved innovation, mainly in the mentioned machinery industry which is trapped by cost and innovation pressure. Thus, innovative units as well as local institutions and individuals have to interact with each other and with their external environment because collaboration with suppliers, customers and competitors enables a firm to deepen its existing technological competence. Moreover, collaboration with research organizations helps a firm broaden its technological knowledge and firms can acquire new scientific knowledge to benefit their product or process innovations by interacting formally and informally with universities and research institutes. The aim of this paper is the identification and evaluation of specific important determinants of innovative activities that influence the economic growth of enterprises in the machinery industry in the Czech Republic by using own multiple regression models. Selected determinants of innovative activities are (i) total turnover, (ii) R&D expenditures, acquisition of external knowledge and total innovation expenditure, (iii) significant market, (iv) membership of a group of enterprises, (v) implementation of innovated goods, (vi) public financial support. For the data analysis we used a harmonized questionnaire of EU Member States from the Community Innovation Survey that was carried out in the Czech Republic for the period 2010 ? 2012. In total, the analysis was performed on data of 284 Czech enterprises from the machinery industry with at least 10 employees. We can say that the greatest influence on the dependent variable was analyzed in determinants of the market supported by the government, and support by EU funds. Results show that there are large numbers of factors that affect the innovation activity, but their significance are marginal.
Keywords: D83; O32; R11; R59; 330; innovation; innovative collaboration; knowledge economy; machinery industry